Autophosphorylation sites participate in the activation of the double-stranded-RNA-activated protein kinase PKR. - Taylor, D R (1996)
The interferon-induced RNA-dependent protein kinase PKR is found in cells in a latent state. In response to the binding of double-stranded RNA, the enzyme becomes activated and autophosphorylated on several serine and threonine residues. Consequently, it has been postulated that autophosphorylation is a prerequisite for activation of the kinase. We report the identification of PKR sites that are autophosphorylated in vitro concomitantly with activation and examine their roles in the activation of PKR. Mutation of one site, threonine 258, results in a kinase that is less efficient in autophosphorylation and in phosphorylating its substrate, the initiation factor eIF2, in vitro. The mutant kinase is also impaired in vivo, displaying reduced ability to inhibit protein synthesis in yeast and mammalian cells and to induce a slow-growth phenotype in Saccharomyces cerevisiae. Mutations at two neighboring sites, serine 242 and threonine 255, exacerbated the effect. Taken together with earlier results (S. B. Lee, S. R. Green, M. B. Mathews, and M. Esteban, Proc. Natl. Acad. Sci. USA 91:10551-10555, 1994), these data suggest that the central part of the PKR molecule, lying between its RNA-binding and catalytic domains, regulates kinase activity via autophosphorylation.